New tools and opportunities in growth and climate friendly greening for small and medium enterprises in the European Union - Szanyi-Gyenes, Xénia; Mudri, György; Bakosné Böröcz, Mária (Applied Studies in Agribusiness and Commerce, 2015)
The role of Small and Medium Enterprises (SMEs) is unquestionable in the European economies, while financial opportunities are still inadequate for them. The more than 20 million SMEs play a significant role in European economic growth, innovation and job creation. According to the latest EC Annual Report , SMEs are accounting for 99% of all non-financial enterprises, employing 88.8 million people and generating almost EUR 3.7 tn in added value for our economy. Despite the fact that there is plenty of EU funding available for these SMEs, for certain reasons these funds hardly reach them. But we have to see that the EU supports SMEs by various way, e.g. by grants, regulatory changes, financial instrument, direct funds. On the other hand, SMEs and decision makers realised that the environmental sustainability has to be attached to the economic growth, therefore more and more tools are available for these enterprises. Over the last few years, public institutions, the market, the financial community and non-governmental associations have explicitly demanded that firms improve their environmental performance. One of the greatest opportunities might lay in the Climate- and Energy Strategy till 2030 as 20% of the EU budget is allocated to climate-related actions, however the easy access to finance is still a key question. Does the EU recognise the actual difficulties? Is there a systemic reason behind the absorption problems? Is the EU creating a more businessfriendly environment for SMEs, facilitating access to finance, stimulates the green and sustainable growth and improving access to new markets? The paper analyses the current European situation of the SMEs and the effectiveness of some new tools, which are specially targeting SMEs.JEL classification: Q18